The scientific literacy of Australian students : science achievement of students in Australian primary and lower secondary schools - Rosier, Malcolm John.; Banks, Diana K. (Hawthorn, Vic. : Australian Council for Educational Research, 1990)
This book provides knowledges about Science Curricula in australia; Populations and Samples; Tests and Questionnaires; Student background Characteristics; Resources for Learning science; ...
Keywords: Science; Educational tests; Educational measurements; Science -- Study and teaching (Primary) -- Australia; Educational tests and measurements -- Australia; Students -- Australia -- Attitudes; Science -- Study and teaching (Secondary) -- Australia